Study of Temperature Characteristics of Micromachined Suspended Coplanar Waveguides for Biosensing Applications - Lijie Li; Zhuming Liu (Sensors, 2011)
In the recent development on biosensors, coplanar waveguide based microwave dielectric sensors have been attracting more and more attentions. In this paper, microwave performance of a suspended coplanar waveguide subject to temperature variations, particularly in a small range, is studied. The prototype is realized through a MEMS fabrication foundry. The thermal transfer analysis of the device is conducted using finite element method, and the microwave properties of the device are characterized. One of the results shows that at 20 GHz, the S11 has decreased by 7.4%, and S21 has increased by 3.5% when the voltage applied to the heaters varies from 9 V to 29 V.